1999
DOI: 10.1515/jpem.1999.12.3.397
|View full text |Cite
|
Sign up to set email alerts
|

Month of Birth and Subsequent Development of Type I Diabetes (IDDM)

Abstract: The aim of this study was to find out whether there is a seasonal pattern in the month of birth of children with IDDM in Israel and whether this pattern, if present, differs from that of total live births. One thousand and ninety-five out of 1,188 children and adolescents (0-17 years) who developed IDDM in Israel between 1980-1993 and whose month of birth was known were included in the study. Separate analysis was made for Jews (n = 987) who have a high incidence (10-18/105) and Arabs (n = 108) with a low inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 19 publications
3
18
1
Order By: Relevance
“…Our search for significant sea- Rothwell et al (1996) report [12], b data from Spain exclude patients born on the 1st of January as that date was over-represented in the set and we assume that it was used to substitute the missing value for date of birth sonality of birth in populations of patients with childhood onset Type I diabetes in 14 European regions outside of Great Britian failed to find any evidence of a seasonal pattern. The grouping of countries into areas of high, medium and low incidence did not show any degree of seasonal effect [17] although differences between high and low incidence groups have been observed in Israel [14].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our search for significant sea- Rothwell et al (1996) report [12], b data from Spain exclude patients born on the 1st of January as that date was over-represented in the set and we assume that it was used to substitute the missing value for date of birth sonality of birth in populations of patients with childhood onset Type I diabetes in 14 European regions outside of Great Britian failed to find any evidence of a seasonal pattern. The grouping of countries into areas of high, medium and low incidence did not show any degree of seasonal effect [17] although differences between high and low incidence groups have been observed in Israel [14].…”
Section: Discussionmentioning
confidence: 77%
“…In 1996, an investigation of a large cohort of children with Type I diabetes from Scotland, Yorkshire and England and Wales in Great Britain found a statistically significant asymmetry in the monthly birth patterns of children who develop Type I diabetes compared with the monthly birth patterns of the background population [12]. Seasonality of birth has also been observed in Sweden [13], in Israel, among Jews [14], and in the Netherlands where differences between males and females have been found [15].…”
mentioning
confidence: 99%
“…One might assume that autoimmune diseases haveddespite different antigens and antibodiesda common trigger in the initiation of an autoimmune process such as viral infections or vitamin D level in the fetal or perinatal period (25). In a series of epidemiologic studies performed in different populations, it has been reported that children and adolescents with type 1 diabetes or autoimmune diseases such as celiac disease and thyroiditis have a different rhythmic pattern of month of birth (25)(26)(27)(28)(29). In an Australian study, there was an inverse correlation between ambient ultraviolet radiation in the first trimester and risk of MS (30).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism may explain the low incidence of T1DM in certain populations and the lack of seasonality of birth in them [Ye Chen et al, 1998; Figure 2. Opposing seasonalities of month of onset of disease and month of birth of the same cohort of Israeli Yemenite Jewish children (0-17 years) with Type 1 diabetes mellitus [data from Laron et al, 1998]. Kida et al, 2000;Collado-Mesa et al, 2001].…”
Section: Initiation Of the Autoimmune Process Of Type 1 Diabetes Begimentioning
confidence: 99%